2013
DOI: 10.1136/bmjopen-2013-003857
|View full text |Cite
|
Sign up to set email alerts
|

Asthma and risk of non-respiratory tract infection: a population-based case–control study

Abstract: ObjectivesAsthmatics have increased risks of airway-related infections. Little is known about whether this is true for non-airway-related serious infections such as Escherichia coli bloodstream infection (BSI). We assessed whether asthma is associated with a risk of developing community-acquired E coli BSI.DesignThe study was designed as a population-based retrospective case–control study.SettingThis population-based study was conducted in Olmsted County, Minnesota.ParticipantsThe study included 259 all eligib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 41 publications
1
22
1
Order By: Relevance
“…Previous studies have reported that impaired innate immune factors may predispose to infection, particularly rhinovirus, Streptococcus pneumoniae, Salmonella enteritidis, and Escherichia coli [19,20]. The mechanism in effect indicates that allergic sensitization can induce similar impairment of innate immunity through toll-like receptor signal transduction.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have reported that impaired innate immune factors may predispose to infection, particularly rhinovirus, Streptococcus pneumoniae, Salmonella enteritidis, and Escherichia coli [19,20]. The mechanism in effect indicates that allergic sensitization can induce similar impairment of innate immunity through toll-like receptor signal transduction.…”
Section: Discussionmentioning
confidence: 98%
“…78 We recently reported the association between asthma and an increased risk of community-acquired E coli BSI in a population-based case-control study (adjusted OR, 2.74; 95% CI, 1.11-6.76; P =.03). 52 Food allergy only approached statistical significance for the association (adjusted OR, 3.51; 95% CI, 0.94-13.1; p =.06), and other atopic conditions were not associated. In our study, there was no evidence of a differential asthma effect across age strata.…”
Section: Effect Of Atopic Conditions On the Risk Of Microbial Infectionsmentioning
confidence: 89%
“…51 Recently, a population-based epidemiologic study showed a significantly increased risk of community-acquired Escherichia coli bloodstream infection (BSI) in persons with asthma compared with those without asthma (discussed in the next section). 52 …”
Section: Effect Of Atopic Conditions On the Risk Of Microbial Infectionsmentioning
confidence: 99%
“…Another study reported that oral corticosteroid therapy among patients using vitamin D resulted in a reduced risk of pneumonia. 71 Also, it has been found that ICS does not account for the association of atopic conditions with risks of various microbial infections 577273,7475,7656 Systemic corticosteroid therapy does not influence humoral or cell-mediated responses to vaccines or increase the risk of clinical infection. 77-81 …”
Section: Factors In the Relationship Between Atopic Conditions Andmentioning
confidence: 99%